La aplicación de la metodología Kaisen y su incidencia en la gestión de empresa Bona Logistic E.I.R.L. período 2017 - Mendez Garcia, Leonardo Martin Alejandro (2018)
Companies in the metal-mechanic sector have focused so much on just producing that they have left quality aside, as well as observing the processes involved in said production. The truth is that being a company and focusing on only one area of it has generated the question of why the effort is not in line with growth, improvement of management or results. The purpose of this research is to observe and determine the effect of the application of the Kaizen methodology in the management of a mechanical metal company Bona Logistic E.I.R.L. in the 2017 period. For this purpose, a comprehensive study of the company was carried out, gathering administrative, accounting, economic and financial information for the 2016 and 2017 periods, applying a deductive - inductive methodology. By virtue of this, the structural and operational situation of the company was analyzed in order to determine the shortcomings that existed in the different areas. The results found can be seen that the entity has not carried out financial, economic, accounting or administrative planning. The improvement in the management of the company product of the application of the Kaizen methodology is the clear and precise evidence that the present research has contributed in an integral and positive way.